Einfluss von Paarinteraktion auf die Gesundheit: Implikationen für die Psychotherapie - Frisch, Judith; Aguilar-Raab, Corina; Eckstein, Monika; Ditzen, Beate (Psychotherapeut, 2017)
Satisfying couple relationships have positive implications for physical and mental health. It is hypothesized that this effect is caused by a reduction of psychobiological stress in stable couple relationships. At the same time, little is known about how specific interpersonal aspects of happy relationships contribute to this correlation. This article provides an overview about research examining the effects of negative and positive couple interactions on health measures. Laboratory studies, field studies and longitudinal studies are described. Furthermore, different neurobiological mediators are discussed (e.g. oxytocin, dopamine, serotonin and endogenous opioids), which influence social processes and are held responsible for the rewarding effects of social interaction. Finally, the psychotherapeutic implications and clinical applications for individual and couple therapy are presented.
Gesehen am 11.05.2018